Implementasi Keperawatan Foot Massage Pada Pasien Hipertensi Dengan Masalah Gangguan Pola Tidur - Putri, Prahardian; Jawiah, Jawiah; Amelia, Riski (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2025)
Background: Hypertension is defined as an increase in blood pressure above the normal threshold, namely systolic pressure exceeding 140 mmHg and diastolic pressure exceeding 90 mmHg. This condition is generally influenced by lifestyle factors such as unhealthy eating habits, being overweight (obesity), lack of sleep, and stress. One relaxation method that can be applied to overcome sleep pattern disorders in hypertensive patients is foot massage therapy. Methods: The case study design in this research uses a descriptive method with a nursing care approach. The research subjects consisted of two patients suffering from hypertension, each aged 65 years, who both experienced similar problems, namely disturbed sleep patterns. This research was carried out in the inpatient room of the Palembang Muhammadiyah Hospital. Data collection was carried out through observation, interviews, and filling out case study instruments during the three-day treatment period. Result: Result were obtained after non-pharmacological implementation: massage therapy (Foot Massage) in patients with sleep pattern disorders there was a decrease in sleep pattern disorders in patient 1 on the 1st day of the psqi assessment was at 10 and on the last day it was at 5. Meanwhile, in patients on the 1st day 2 of the psqi assessment was at 10 and the final result was at 5. Conclusion: The implementation of foot massage relaxation therapy can help reduce sleep pattern disorders in hypertensive patients